The Gut-Brain Axis in Multiple Sclerosis. Is Its Dysfunction a Pathological Trigger or a Consequence of the Disease? - Parodi, Benedetta; Kerlero de Rosbo, Nicole (Frontiers in Immunology, 2021)
A large and expending body of evidence indicates that the gut-brain axis likely plays a crucial role in neurological diseases, including multiple sclerosis (MS). As a whole, the gut-brain axis can be considered as a bi-directional multi-crosstalk pathway that governs the interaction between the gut microbiota and the organism. Perturbation in the commensal microbial population, referred to as dysbiosis, is frequently associated with an increased intestinal permeability, or “leaky gut”, which allows the entrance of exogeneous molecules, in particular bacterial products and metabolites, that can disrupt tissue homeostasis and induce inflammation, promoting both local and systemic immune responses. An altered gut microbiota could therefore have significant repercussions not only on immune responses in the gut but also in distal effector immune sites such as the CNS. Indeed, the dysregulation of this bi-directional communication as a consequence of dysbiosis has been implicated as playing a possible role in the pathogenesis of neurological diseases. In multiple sclerosis (MS), the gut-brain axis is increasingly being considered as playing a crucial role in its pathogenesis, with a major focus on specific gut microbiota alterations associated with the disease. In both MS and its purported murine model, experimental autoimmune encephalomyelitis (EAE), gastrointestinal symptoms and/or an altered gut microbiota have been reported together with increased intestinal permeability. In both EAE and MS, specific components of the microbiota have been shown to modulate both effector and regulatory T-cell responses and therefore disease progression, and EAE experiments with germ-free and specific pathogen-free mice transferred with microbiota associated or not with disease have clearly demonstrated the possible role of the microbiota in disease pathogenesis and/or progression. Here, we review the evidence that can point to two possible consequences of the gut-brain axis dysfunction in MS and EAE: 1. A pro-inflammatory intestinal environment and “leaky” gut induced by dysbiosis could lead to an altered communication with the CNS through the cholinergic afferent fibers, thereby contributing to CNS inflammation and disease pathogenesis; and 2. Neuroinflammation affecting efferent cholinergic transmission could result in intestinal inflammation as disease develops.